The Role of Scholarship in University Teaching - Taylor, K. Lynn (Canadian Journal of Higher Education, 1993)
The primary resource in university teaching is the scholarship of faculty. This discussion paper explores the potential role of scholarship as a teaching resource and the value of a scholarship perspective in instructional development. It is argued that the content, structure and process knowledge inherent in scholarship have the potential to contribute to effective teaching and learning, but only when all three forms of expert knowledge are explicitly taught. This teaching task does not flow naturally from scholarship, but requires reflection and careful structuring on the part of the scholar-teacher. It is also argued that a scholarship perspective constitutes an effective context from which to engage a broader spectrum of faculty in communicating about teaching and learning. The purpose of this paper is to stimulate discussion on how a scholarship-based instructional development context might achieve learning outcomes that more closely approximate the ideal of apprenticeship in a discipline.